The Deletion of Hdac4 in Mouse Osteoblasts Influences Both Catabolic and Anabolic Effects in Bone. (25th April 2018) - Nakatani, Teruyo; Chen, Tiffany; Johnson, Joshua; Westendorf, Jennifer J; Partridge, Nicola C
ABSTRACT: Histone deacetylase 4 (Hdac4) is known to control chondrocyte hypertrophy and bone formation. We have previously shown that parathyroid hormone (PTH) regulates many aspects of Hdac4 function in osteoblastic cells in vitro; however, in vivo confirmation was previously precluded by preweaning lethality of the Hdac4 ‐deficient mice. To analyze the function of Hdac4 in bone in mature animals, we generated mice with osteoblast lineage‐specific knockout of Hdac4 ( Hdac4 ob‐/‐ ) by crossing transgenic mice expressing Cre recombinase under the control of a 2.3‐kb fragment of the Col1a1 promoter with mice bearing loxP‐ Hdac4 . The Hdac4 ob‐/‐ mice survive to adulthood and developed a mild skeletal phenotype. At age 12 weeks, they had short, irregularly shaped and stiff tails due to smaller tail vertebrae, with almost no growth plates. The tibial growth plate zone was also thinned, and Mmp13 and Sost mRNAs were increased in the distal femurs of Hdac4 ob‐/‐ mice. Immunohistochemistry showed that sclerostin was elevated in Hdac4 ob‐/‐ mice, suggesting that Hdac4 inhibits its gene and protein expression. To determine the effect of PTH in these mice, hPTH (1‐34) or saline were delivered for 14 days with subcutaneously implanted devices in 8‐week‐old female Hdac4 ob‐/‐ and wild‐type ( Hdac4 fl/fl ) mice. Serum CTX, a marker of bone resorption, was increased in Hdac4 ob‐/‐ mice with or without PTH treatment. Tibial cortical bone volume/total volume (BV/TV), cortical thickness (Ct.Th), and relative cortical area (RCA) were decreased in Hdac4 ob‐/‐ mice, but PTH caused no further decrease in Hdac4 ob‐/‐ mice. Tibial trabecular BV/TV and thickness were not changed significantly in Hdac4 ob‐/‐ mice but decreased with PTH treatment. These results indicate that Hdac4 inhibits bone resorption and has anabolic effects via inhibiting Mmp13 and Sost /sclerostin expression. Hdac4 influences cortical bone mass and thickness and knockout of Hdac4 prevents the catabolic effect of PTH in cortical bone. © 2018 American Society for Bone and Mineral Research.